Initial experience with aneurysm coiling in Nepal - Rajbhandari, Pravesh; Neupane, Anish; Rajbhandari, Saujanya; Shrestha, Pranaya; Acharya, Samir; Shrestha, Resha; Rajbhandari, Reema; Sharma, Avinash; Upadhya, Sagar; Dhungel, Pragya; Matin, Tariq; Pant, Basant (Nepal Journal of Neuroscience, 2018)
The aim of this study is to show the result of aneurysm coiling despite the difficulty in initiating neurointervention in Nepal. It is a retrospective study where only aneurysm that has undergone coiling are taken from 2017 to 2018.A total of eleven patients (male: female = 1: 10) with aneurysm were treated with Endovascular therapy. 9 cases were ruptured aneurysm while 3 were unruptured. 5 aneurysm were located in anterior circulation while 6 were located in posterior circulation. Out of eleven cases 4 were treated by simple coiling technique, while 2 underwent balloon assisted coiling, 3 stent assisted coiling, 1 pConus assisted coiling and 1 simple coiling and stent assisted coiling. Statistical analysis showed significant correlation between fisher grading scale with mRS score (P=0.013) suggesting lower fisher grade, and improved outcome similar to the result of prospective one year follow up of Barrow Ruptured Aneurysm Trial ( BRAT) study. With limited resources aneurysm coiling was performed at ANIAS with similar results to literature. Nepal Journal of Neuroscience, Volume 15, Number 2, 2018, page: 30-35